Relationship between psychological characteristic and entrepreneurial inclination among students of Universiti Teknologi Mara Kampus Bandaraya Melaka / Izzati Ayuni Azmir - Azmir, Izzati Ayuni (Faculty of Business and Management, 2015)
As Malaysia entered the twenty first century, interest and concerns on the subject of entrepreneurship heightened among others. Entrepreneurship has become one of the main forces that contributed towards the economic growth and job creation. A lot of research has been conducted throughout the world, which mostly focus on the young entrepreneurs. The impact of psychological characteristics such as (locus of control, need for achievement, tolerance for ambiguity, innovation, self confidence, and propensity to risk taking) has been recognized as some of the main factors that contribute towards youth’s inclination on being an entrepreneur. Thus, this study focuses on the relationship between psychological factors and entrepreneurial inclination of Universiti Teknologi MARA Kampus Bandaraya Melaka undergraduates students. Based on the literature reviews, hypothesis were established to investigate the relationship between psychological characteristics and entrepreneurial inclination. The hypothesis were tested by using the data collected through personally administered questionnaires. A total of 341 questionnaires have been distributed to Universiti Teknologi MARA Kampus Bandaraya Melaka students. The questionnaires consist of 41 items were analyzed by using Statistical Package for the Social Sciences (SPSS) software.